The UKIRT Hemisphere Survey: definition and J-band data release. Issue 4 (9th October 2017) - Dye, S.; Lawrence, A.; Read, M. A.; Fan, X.; Kerr, T.; Varricatt, W.; Furnell, K. E.; Edge, A. C.; Irwin, M.; Hambly, N.; Lucas, P.; Almaini, O.; et al.
Abstract: This paper defines the UK Infra-Red Telescope (UKIRT) Hemisphere Survey (UHS) and release of the remaining ∼12 700 deg 2 of J -band survey data products. The UHS will provide continuous J - and K -band coverage in the Northern hemisphere from a declination of 0° to 60° by combining the existing Large Area Survey, Galactic Plane Survey and Galactic Clusters Survey conducted under the UKIRT Infra-red Deep Sky Survey (UKIDSS) programme with this new additional area not covered by UKIDSS. The released data include J -band imaging and source catalogues over the new area, which, together with UKIDSS, completes the J -band UHS coverage over the full ∼17 900 deg 2 area. 98 per cent of the data in this release have passed quality control criteria. The remaining 2 per cent have been scheduled for re-observation. The median 5σ point source sensitivity of the released data is 19.6 mag (Vega). The median full width at half-maximum of the point spread function across the data set is 0.75 arcsec. In this paper, we outline the survey management, data acquisition, processing and calibration, quality control and archiving as well as summarizing the characteristics of the released data products. The data are initially available to a limited consortium with a world-wide release scheduled for 2018 August.